2009
DOI: 10.1192/pb.bp.107.019075
|View full text |Cite
|
Sign up to set email alerts
|

Non-medical prescribing: the story so far

Abstract: Non-medical prescribing is an element of the National Health Service modernisation agenda intended to change traditional professional roles and responsibilities, as part of New Ways of Working. This article describes concepts of non-medical prescribing and its implications for UK psychiatric practice. the perceived benefits of non-medical prescribing cannot be denied but debate continues about competence and clinical governance issues. Psychiatrists have an essential role to play in the success of non-medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Self‐reported bias to this question cannot entirely be excluded even though it did not directly reflect upon the respondents themselves. Some non‐medical prescribing courses have been reported by Kwentoh & Reilly (2009) as being focused on generic training with little mental health content. Concerns about training are being addressed by some Trusts which have arranged additional teaching (Gray et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self‐reported bias to this question cannot entirely be excluded even though it did not directly reflect upon the respondents themselves. Some non‐medical prescribing courses have been reported by Kwentoh & Reilly (2009) as being focused on generic training with little mental health content. Concerns about training are being addressed by some Trusts which have arranged additional teaching (Gray et al .…”
Section: Discussionmentioning
confidence: 99%
“…Independent prescribers rightly argue that they are legally on par with medical prescribers. Kwentoh & Reilly (2009) found that independent prescribers prescribe appropriately when supervised by medically trained assessors. Reassuringly, all our respondents said that they would seek advice from a psychiatrist when needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation